Effect of Most Favored Regions of Estrogen Receptor β (ERβ) Molecules on MolDock Score Using Tamoxifen Ligand - Salmasfattah, Novyananda; Permata, Agung; Prasetyawan, Fendy (Yayasan Pendidikan Tanggui Baimbaian, 2024)
The estrogen receptor β (ERβ) molecule is one of the target proteins in cancer treatment. The type of ERβ molecule in the protein data bank (PDB) determines the value of most favored regions and MolDock score. The purpose of this study was to determine the effect of most favored regions of ERβ molecules on MolDock score using Tamoxifen ligand. There are 37 molecules that have ERβ protein, 7 molecules were selected to be analyzed for the value of most favored regions and MolDock score, based on the r table value, pearson correlation value 0.548 < 0.754 (r table). This is also the same when viewed from the significance value of 0.203 > 0.05. It can be concluded that there is no correlation between the value of most favored regions and MolDock score.